2019
DOI: 10.15585/mmwr.ss6801a1
|View full text |Cite
|
Sign up to set email alerts
|

Foodborne Illness Outbreaks at Retail Establishments — National Environmental Assessment Reporting System, 16 State and Local Health Departments, 2014–2016

Abstract: Problem/Condition State and local public health departments report hundreds of foodborne illness outbreaks each year to CDC and are primarily responsible for investigations of these outbreaks. Typically, investigations involve epidemiology, laboratory, and environmental health components. Health departments voluntarily report epidemiologic and laboratory data from their foodborne illness outbreak investigations to CDC through the Foodborne Disease Outbreak Surveillance System (FDOSS); however, min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 10 publications
(18 reference statements)
1
19
0
Order By: Relevance
“…Perhaps the presence of noticeable debris on workers' hands from working with raw food makes workers more inclined to wash their hands appropriately. However, in multiple subsequent studies, compliance with provision G continued to be suboptimal (2,17,89,97).…”
Section: Compliance With Food Code Recommendationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Perhaps the presence of noticeable debris on workers' hands from working with raw food makes workers more inclined to wash their hands appropriately. However, in multiple subsequent studies, compliance with provision G continued to be suboptimal (2,17,89,97).…”
Section: Compliance With Food Code Recommendationsmentioning
confidence: 99%
“…The lack of specificity of the Food Code recommendation may account in part for differences in glove policies in retail establishments. In a 2014 to 2016 survey, most establishments required gloves when handling ready-to-eat foods and when workers had cuts or other skin injuries, but only half required gloves to be worn at all times when working in a kitchen (89). The same survey revealed that bare-hand contact by potentially infectious workers (food handlers and preparers) was one of the top 10 factors contributing to outbreaks in retail food service establishments (89).…”
Section: Glove Usementioning
confidence: 99%
See 2 more Smart Citations
“…Improved transportation, particularly the cold-chain, is an important reason for globalization of the food supply [10]. Consequently, foodborne disease outbreaks today are less likely to be limited geographically, and international foodborne disease outbreaks have become more common [11,12]. One example is recurrent outbreaks of cyclosporosis in the USA associated with imported fresh produce [13].…”
Section: Globalization Of Food Supplymentioning
confidence: 99%